Communication Strategy on Agricultural Insurance in South Kalimantan - Alif, Muhammad; ., Sumardjo; Sarwoprasodjo, Sarwititi; Fatchiya, Anna (Communicatus: Jurnal Ilmu komunikasi, 2022)
This study aims to analyze the communication strategy of the agricultural insurance program in the South Kalimantan region to create superior and independent farmers. This communication strategy can contribute to existing development programs in the South Kalimantan region. This research used qualitative methods with SWOT and TOWS analysis techniques. Data collection techniques were open interviews, focus group discussions (FGD), and field observations (research locations and district level). The results of the study showed that agricultural insurance in the South Kalimantan region had obstacles that occurred in the field, many farmers needed help understanding and were not interested in participating in this rice farming insurance. First, the analysis of the agricultural insurance communication strategy in the SWOT analysis in the South Kalimantan region was to increase the quality capacity of government human resources in the field by providing socialization technical training and involving opinion leaders, groups, and village governments in disseminating information. Second, the communication strategy in the TOWS analysis was to optimize the existing social capital in the community, form an information centers at the village level, add variety and diversity in the methods of conveying information by extension workers and Jasindo officers and provide a variety of media sources of information, especially social media, and internet. The agricultural insurance communication strategis important to policymakers in implementing development programs.